Cultivation of microalgae in food processing effluent for pollution attenuation and astaxanthin production: a review of technological innovation and downstream application - Zhang, Xiaowei; Lu, Qian (Frontiers in Bioengineering and Biotechnology, 2024)
Valorization of food processing effluent (FPE) by microalgae cultivation for astaxanthin production is regarded as a potential strategy to solve the environmental pollution of food processing industry and promote the development of eco-friendly agriculture. In this review paper, microalgal species which have the potential to be employed for astaxanthin in FPE were identified. Additionally, in terms of CO2 emission, the performances of microalgae cultivation and traditional methods for FPE remediation were compared. Thirdly, an in-depth discussion of some innovative technologies, which may be employed to lower the total cost, improve the nutrient profile of FPE, and enhance the astaxanthin synthesis, was provided. Finally, specific effects of dietary supplementation of algal astaxanthin on the growth rate, immune response, and pigmentation of animals were discussed. Based on the discussion of this work, the cultivation of microalgae in FPE for astaxanthin production is a value-adding process which can bring environmental benefits and ecological benefits to the food processing industry and agriculture.Particularly, technological innovations in recent years are promoting the shift of this new idea from academic research to practical application. In the coming future, with the reduction of the total cost of algal astaxanthin, policy support from the governments, and further improvement of the innovative technologies, the concept of growing microalgae in FPE for astaxanthin will be more applicable in the industry.